2010
DOI: 10.1021/cm903767n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Mesoporous Ta−W Oxides as Strong Solid Acid Catalysts

Abstract: Several mesoporous Ta x W10−x mixed oxides prepared from TaCl5 and WCl6 in the presence of poly block copolymer surfactant Pluronic P-123 were examined as potential solid acid catalysts. Amorphous wormhole-type mesopores were observed in samples with x values from 3 to 10, whereas W-rich samples (x = 0−2) formed nonmesoporous structures with crystallized tungsten oxide (WO3). The acid strength increased with addition of W for mesoporous Ta x W10−x oxides, and mesoporous Ta3W7 oxide exhibited the highest acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…Interestingly, the TOF number of the s-CER/PVA composite (s-CER: PVA=3: 2) was approximately 3.3 and 2.6 times greater than that of s-CER and sulfuric acid, respectively, indicating the higher intrinsic catalytic activity of the s-CER/PVA composite. 44,45 As pointed out earlier, the highly hydrophilic -OH sites in PVA can facilitate the absorption of H 2 O in the reaction mixture by the PVA dominated region and thus liberate the -SO 3 H sites that would otherwise be blocked by H 2 O molecules in s-CER or SO 4 indicates that a greater number of -SO 3 H were utilized in s-CER/PVA for esterification due to water absorption by PVA. The composites with s-CER: PVA mass ratio of 3: 2 had the highest TOF number among all the s-CER/PVA, suggesting that the PVA content had little effect on the intrinsic catalytic activity after -OH content reached a critical value (PVA mass ratio of 40.0 %).…”
Section: Specific Role Of Pvamentioning
confidence: 91%
“…Interestingly, the TOF number of the s-CER/PVA composite (s-CER: PVA=3: 2) was approximately 3.3 and 2.6 times greater than that of s-CER and sulfuric acid, respectively, indicating the higher intrinsic catalytic activity of the s-CER/PVA composite. 44,45 As pointed out earlier, the highly hydrophilic -OH sites in PVA can facilitate the absorption of H 2 O in the reaction mixture by the PVA dominated region and thus liberate the -SO 3 H sites that would otherwise be blocked by H 2 O molecules in s-CER or SO 4 indicates that a greater number of -SO 3 H were utilized in s-CER/PVA for esterification due to water absorption by PVA. The composites with s-CER: PVA mass ratio of 3: 2 had the highest TOF number among all the s-CER/PVA, suggesting that the PVA content had little effect on the intrinsic catalytic activity after -OH content reached a critical value (PVA mass ratio of 40.0 %).…”
Section: Specific Role Of Pvamentioning
confidence: 91%
“…Nevertheless, the sol-gel strategy, directly incorporating tungsten species into metal oxide composites, is supposed to afford a homogenous distribution of tungsten oxide, as well as a high stability for anti-aggregation. [18][19][20][21][22] Mesoporous TiO 2 is widely studied due to the variety of its potential applications. 23 It was reported that the crystallization temperature of TiO 2 was much lower than that of tungsten oxide, 24 and the solid solution of TiO 2 and WO 3 was formed over 700 C.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous Nb-W and Ta-W mixed oxides were found to exhibit remarkable acid catalytic activity for Friedel-Crafts alkylation and the hydrolysis of sugars and esterification, surpassing conventional solid acids owing to their high surface area, mesoporous structure, and strong Brønsted acid sites (−12 ≤ H 0 < −6.6) [61,62]. In addition, mesoporous Nb-W and Ta-W oxides have the significant advantages of recyclability and thermal stability.…”
Section: New Catalytic Systemsmentioning
confidence: 99%
“…Water-tolerant solid acids, such as layered HNbMoO 6 [55,151], HTaMoO 6 [54], mesoporous Nb-W oxides [61], and Ta-W oxides [62], showed high activity for cellobiose hydrolysis, a unit of cellulose. The high performance of layered oxides is attributed to facile intercalation of cellobiose into the interlayer gallery containing strong Brønsted acid sites.…”
Section: Hydrolysis Of Cellulosementioning
confidence: 99%